Diagnóstico de las Conductas Agresivas de los niños y niñas de la I.E N°224 Indoamerica, 2017 - Cotrina Huamán, Katerine del Rosario (2018)
The present research work has been oriented to determine the diagnosis of the aggressive behaviors of the children of the I.E N° 224 Indoamerica, from the city of Trujillo - Buenos Aires. To carry out the work, a sample population of 196 children of 3, 4 and 5 years of age was used from the I.E N° 224 Indoamerica. In the research has been used the descriptive design._x000D_ The present research work has been oriented to determine the diagnosis of the aggressive behaviors of the children of the I.E N° 224 Indoamerica, from the city of Trujillo – Buenos Aires._x000D_ To carry out the work, a sample population of 196 children of 3, 4 and 5 years of age was used from the I.E N° 224 Indoamerica. In the research has been used the descriptive design. To measure the level of aggressive behavior of children of the institution before mentioned applied as instrument the value scale._x000D_ In the observations made during the recess of the boys and girls, the level of their aggressive behavior is identified, which helped us to diagnose the level in which the entire educational institution is located._x000D_ It has been determined, after having applied the evaluation scale, that the childre of the I.E N° 224 Indoamerica have a high level of aggressive behavior. This is verified in our statistical results where they reached a high level with 51.53%, medium level with 28.06% and a low level with 20.41%._x000D_ We hope that the results obtained in the present investigation will serve the institution and mainly the teachers involved in their education in order to develop affectionate girls and boys who love and respect themselves as the others.